HOLISTIC LIFE SPIRITUALITY INSPIRATION FROM HENRICUS LEVEN - Lusia Kolir Assan; Maria Fransiska Entali Kedang; Lusia Lodan Odjan; Yohanes Hermianus (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Holistic spirituality is an approach to life that integrates the physical, mental, social, and religious dimensions. In the context of the rapid development of modern society, the concept of holistic spirituality is increasingly relevant as a response to the crisis of meaning, stress, and human alienation. This article examines Hendrikus Leven's ideas on holistic spirituality, which emphasize self-balance, harmonious relationships with others, and a deep connection with God and the universe. Through a descriptive-analytical approach, this discussion illustrates the contribution of Leven's thinking to enriching the understanding of modern spirituality, including its relevance to personal life, education, pastoral care, and character development. This study concludes that Hendrikus Leven's holistic spirituality can become a paradigm for life renewal that touches all aspects of human existence and offers a path to building a more meaningful, balanced, and sustainable life.